Fostering Ethical Professional Identity in Tax: Using the Traditional Tax Classroom - Field, Heather M. (Columbia Journal of Tax Law, 2017)
Who will today’s tax law students be as legal professionals? How will they build sustainable, impactful, and ethical careers in tax law? Students should develop an ethical professional identity, and law schools must help students in this endeavor. The Carnegie Report of 2007 argued that law schools must incorporate professional identity development into legal education.[3] The CLEA Report, another 2007 report on legal education reform, also highlighted professional identity formation as a core objective for legal education.[4] These reports led to a flurry of academic articles and books about professional identity formation,[5] and at least six schools have now adopted student learning outcomes to the effect that “students should develop a personal code of ethics/moral core to guide discretionary professional decision-making”.